Glycerol-based polyurethane-silica organic-inorganic hybrid as an anticorrosive coating - Braz, Álvaro G. [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Elsevier, 2022)
This work investigates the use of glycerol as a crosslinker for segments of polyurethane (PU), which was hybridized with a silica network employing (3-aminopropyl) triethoxysilane (APTES) as a covalent coupling agent. This organic-inorganic hybrid (OIH) was applied as a protective coating on a steel substrate, using a sol-gel dip coating process. Evaluation was made of the effects of the inorganic components (APTES and tetraethyl orthosilicate (TEOS)) and the PU monomers (4,4′-methylenebis(phenyl isocyanate) (4,4’-MDI)) on the structure, thermal stability, and corrosion protection properties of samples prepared using APTES/4,4’-MDI molar ratios of 0.50, 0.75, 1.00, 1.25, and 1.50. The expected chemical structure of the OIH was confirmed by Fourier transform infrared (FTIR) and nuclear magnetic resonance (13C and 29Si NMR) spectroscopy analyses. Thermogravimetric analysis showed that all the OIH materials presented thermal stability above 200 °C, irrespective of the APTES/4,4’-MDI molar ratio. All the coatings presented low roughness (2.3 to 3.0 nm) and thickness of around 2.0 μm. Electrochemical impedance spectroscopy measurements of the OIH-coated A1020 carbon steel evidenced an impedance modulus exceeding 100 MΩ.cm2 almost 180 days after immersion in saline solution for the PU-silica coating obtained with APTES/4,4’-MDI molar ratio of 1.00. The performance of the PU-silica hybrid presented in this work showed its suitability for application as an anticorrosive thin coating to protect metal alloys against corrosion.
Keywords: Anticorrosive coating; Glycerol; Polyurethane-silica hybrid; Sol-gel process